Upaya Menurunkan Perilaku Menarik Diri pada Orang dengan Gangguan Jiwa (ODGJ) melalui Pendekatan Aktivitas Terapeutik di PSR-GPODGJ - Sawi Sujarwo; Thania Adinda Febiyanti (Yayasan Kawanad, 2026)
Social withdrawal is one of the common problems experienced by people with mental disorders and may hinder social rehabilitation and interpersonal functioning. This condition is characterized by low social participation, limited communication, and a tendency to avoid interaction with others. This activity was conducted at the Graha Peduli Social Rehabilitation Center for People with Mental Disorders (PSR–GPODGJ) Palembang with the aim of helping reduce social withdrawal through therapeutic activities. The method involved an individual intervention conducted over 12 sessions through several stages, including assessment, rapport building, orientation, modeling, therapeutic activities, evaluation, and termination. The activities included emotion cards, picture-guessing exercises, object identification, and simple communication training to develop the participant's social interaction skills. The results showed positive changes in communication skills, confidence in answering questions, ability to maintain conversations, eye contact, and participation in social activities. The participant, who initially tended to be passive, gradually showed greater initiative to interact and provided better responses during the activities. These results suggest that therapeutic activities can serve as an approach to support social rehabilitation and the development of interpersonal skills among people with mental disorders.